2019
DOI: 10.3390/medicina55040113
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension in Asymptomatic Patients with Chronic Kidney Disease

Abstract: Background and objective: Orthostatic hypotension (OH) is a decrease in systolic blood pressure (BP) of 20 mm Hg and in diastolic BP of 10 mm Hg when changing the position from lying to standing. Arterial hypertension (AH), comorbidities and polypharmacy contribute to its development. The aim was to assess the presence of OH and its predictors in asymptomatic chronic kidney disease (CKD) patients. Material and methods: 45 CKD patients with estimated glomerular filtration rate (eGFR) ≤ 60 mL/min/1.73 m2 (CKD+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…There was no difference in the history of falls or fainting between the OH+ and OH-groups. It is in line with earlier studies showing that OH was asymptomatic in the majority of patients [6,13]. If patients are screened for OH based only on clinical symptoms connected with blood pressure fall after standing, the detected prevalence would underestimate the real prevalence [6,8].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was no difference in the history of falls or fainting between the OH+ and OH-groups. It is in line with earlier studies showing that OH was asymptomatic in the majority of patients [6,13]. If patients are screened for OH based only on clinical symptoms connected with blood pressure fall after standing, the detected prevalence would underestimate the real prevalence [6,8].…”
Section: Discussionsupporting
confidence: 89%
“…Chronic kidney disease (CKD) is associated with a high prevalence of OH. In a group of asymptomatic CKD patients (mean age 69 years, eGFR 36 mL/min/1.73m 2 ), the prevalence of OH was 38% [13]. In the present study, KTRs with OH were older and more often diabetic than patients without OH.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…However, as antihypertensive use was in accordance with British Hypertension Society guidelines, it is likely that regimens were similar between patients with similar eGFR. There is no clear evidence suggesting certain antihypertensives are more likely to cause OH in this patient group, with some weak evidence linking beta blockers to OH in some combinations and at some eGFR levels [46]. Chan et al found no significant difference in OH risk between patients on ACE I or ARB medications in a variety of combinations [47], while Sasaki et al found no significant difference in the presence or absence of OH in patients taking calcium antagonists, beta blockers, ACE I or diuretics either before or after initiation of haemodialysis [21].…”
Section: Discussionmentioning
confidence: 82%